1978
DOI: 10.1152/ajpheart.1978.234.4.h416
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic stress-strain relation of nonexcised blood-perfused canine papillary muscle

Abstract: We studied diastolic stiffness of 10 coronary-perfused twitching papillary muscles of the canine right ventricle. The muscle beat at a regular sinus rhythm of 122 +/- 20 (SD) beats/min at 37 degrees C. They were stretched slowly at a constant rate. Diastolic force increased exponentially with the stretch. Calculating Lagrangian stress (sigma) and strain (epsilon) from diastolic force and length, we found a linear relationship between ln sigma and epsilon within the physiological range of strain (0.025 less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The passive tension-sarcomere length relationship of single frog atrial cells appears to be described adequately by an exponential function over the sarcomere length range of about 2.2 fixn to about 3.5 /xm used in the present investigation. The exponential index (a), obtained from the Lagrangian stress-sarcomere length relationships, is on the order of 5.3, which is similar to a value of 6-7, which can be calculated from data on semitendinosus muscle (Moss and Halpern, 1977), but it is considerably less than the values of 18-37 that have been reported for intact mammalian cardiac muscle (Kitabatake and Suga, 1978).…”
Section: Tension-length Relation Of Single Heart Cells/tarr Et Alsupporting
confidence: 59%
See 1 more Smart Citation
“…The passive tension-sarcomere length relationship of single frog atrial cells appears to be described adequately by an exponential function over the sarcomere length range of about 2.2 fixn to about 3.5 /xm used in the present investigation. The exponential index (a), obtained from the Lagrangian stress-sarcomere length relationships, is on the order of 5.3, which is similar to a value of 6-7, which can be calculated from data on semitendinosus muscle (Moss and Halpern, 1977), but it is considerably less than the values of 18-37 that have been reported for intact mammalian cardiac muscle (Kitabatake and Suga, 1978).…”
Section: Tension-length Relation Of Single Heart Cells/tarr Et Alsupporting
confidence: 59%
“…Fung (1967) suggested that the relationships between passive tension and length could be described by an exponential relationship of the form T = T* exp (a) (A-X*), where T is the tension or stress, A is the extension ratio (length divided by nonstressed length), (a) is an exponential index, and T* is the tension (or stress) at a specific extension ratio X*. Such an exponential function has been used to describe the passive tension-length relationships of skeletal muscle (Moss and Halpern, 1977) and cardiac muscle (Kitabatake and Suga, 1978). The passive tension-sarcomere length relationship of single frog atrial cells appears to be described adequately by an exponential function over the sarcomere length range of about 2.2 fixn to about 3.5 /xm used in the present investigation.…”
Section: Tension-length Relation Of Single Heart Cells/tarr Et Almentioning
confidence: 99%
“…We assessed passive stiffness from the stress-strain relationship calculating the elastic constants a and ,8 as described by Glantz and Kernoff (11). Because the stress-strain relationship of cardiac muscle is monoexponential over the physiologic range of stress (11,12), the elastic constants can be derived from: a = a (e#' -1) where a = force/instantaneous cross sectional area and e (Lagrangian strain) = 1 -10/10, 1 being unstressed muscle length. We also calculated the tangent modulus or elastic stiffness (da/ de) from do/de = ,a + #a (11).…”
Section: Methodsmentioning
confidence: 99%
“…Direct evidence for this relationship has been demonstrated in cardiac papillary muscle, which becomes stiffer with increased perfusion (Kitabatake & Suga, 1978). Indirect evidence for an effect of vascular perfusion on upper airway wall stiffness comes from both animal and human experiments.…”
Section: The Effect Of Rem Sleep On the Upper Airwaymentioning
confidence: 99%